Changes in physical activity outcomes in the Strong Hearts, Healthy Communities (SHHC-2.0) community-based randomized trial - Jay E. Maddock; Margaret Demment; Meredith Graham; Sara Folta; David Strogatz; Miriam Nelson; Seong-Yeon Ha; Galen D. Eldridge; Rebecca A. Seguin-Fowler (International Journal of Behavioral Nutrition and Physical Activity, 2022)
Abstract Background Physical inactivity is a risk factor for numerous adverse health conditions and outcomes, including all-cause mortality. Aging rural women are at particular risk for physical inactivity based on environmental, sociocultural, and psychosocial factors. This study reports on changes in physical activity and associated factors from a multicomponent community-engaged intervention trial. Methods Strong Hearts, Healthy Communities 2.0 (SHHC-2.0) was a 24-week cluster (community) randomized controlled trial building on the results from the previous trial of SHHC-1.0. Rural women (n = 182) aged 40 and over living in 11 rural communities in upstate New York were recruited. The intervention consisted of twice-weekly experiential classes focused on exercise, nutrition, and civic engagement. Physical activity outcomes included accelerometry and self-report as well as related psychosocial measures at midpoint (12 weeks) and post-intervention (24 weeks). Data were analyzed using multilevel linear regression models with the community as the random effect. Results Compared to participants from the control communities, participants in the intervention communities showed a significant increase in objectively measured moderate to vigorous intensity physical activity: at 12 weeks (increase of 8.1 min per day, P < 0.001) and at 24 weeks (increase of 6.4 min per day; P = 0.011). Self-reported total MET minutes per week also increased: at 12 weeks (increase of 725.8, P = 0.003) and 24 weeks (increase of 955.9, P = 0.002). Several of the psychosocial variables also showed significant positive changes. Conclusions The SHHC-2.0 intervention successfully increased physical activity level and related outcome measures. Modifications made based upon in-depth process evaluation from SHHC-1.0 appear to have been effective in increasing physical activity in this at-risk population. Trial registration Clinicaltrials.gov: NCT03059472. Registered 23 February 2017.